Rancang Bangun Sistem Informasi Pendataan Tamu Berbasis Web - I Gede Hadi Darmawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Visit of agencies or institutions are something that occurs in the community. Visitors or guests are often recorded in a conventional recorded agenda or book (guest book). This is certainly less effective because it is still done by recording on a physical book that is easily damaged and often raises the queue in of the guest registration. The problem can be solved by designing a web-based information system to record guests or visitors. The result of this research is in the form of websites with the name Hibook that can be used to do the registration of visitor by scanning the QR code through the phone. With this system visitors can easily register a visiting, because they no longer need to write manually or queueing for registration, as well as agencies or institutions no longer need to take care and archiving guest books